A couple returning from Peru with persistent fever: think of histoplasmosis - Steven Van Den Broucke (Elsevier, 2021)
A couple presented with fever and strikingly similar symptoms starting exactly on the same day after returning from an adventurous journey in Peru. Symptom onset was 12 days after exposure to bats from a hollow tree. The further evolution underscores the disparate disease course of Histoplasmosis in different individuals, despite similar radiological findings. Our case highlights the importance of careful history taking in returning travelers since exposure to bat (or fowl) excrement can be easily overlooked.